2006
DOI: 10.1017/phn2006943
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry and body composition of south Indian babies at birth

Abstract: Objectives: To assess the consequences on body composition of increasing birth weight in Indian babies in relation to reported values in Western babies, and to assess the relationship between maternal and neonatal anthropometry and body composition. Design: Prospective observational study. Setting: Bangalore City, India. Subjects: A total of 712 women were recruited at 12.5^3.1 weeks of gestation (mean^standard deviation, SD) and followed up until delivery; 14.5% were lost to follow-up. Maternal body weight, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 27 publications
7
37
3
Order By: Relevance
“…Put another way, the trajectory of a lower-birth-weight baby would be towards a lower BMI and more adverse, centrally adipose phenotype at 8 years of age, a finding comparable to those from other studies (12)(13)(14)(15)(16)(17) .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Put another way, the trajectory of a lower-birth-weight baby would be towards a lower BMI and more adverse, centrally adipose phenotype at 8 years of age, a finding comparable to those from other studies (12)(13)(14)(15)(16)(17) .…”
Section: Discussionsupporting
confidence: 84%
“…Rapid infant growth appeared protective, but rapid later childhood growth (between 6 and 8 years of age) weakly predicted adverse WHR and systolic blood pressure. These trajectories have been identified in other studies (12)(13)(14)(15)(16)(17)(18)(19)(20) . Those in the lowest birth weight tertile remained at higher risk of a high WHR but this was attenuated by faster overall growth.…”
Section: Discussionsupporting
confidence: 73%
“…One often-cited study reported that total fat mass of neonates explained 46% of the variance in birth weight even though adipose comprises only around 12% of total birth weight [10], but whether heavier babies are also proportionally fatter remains unclear. Relative fatness, rather than absolute fat mass, is likely to be a stronger influence on later disease risk and be a more relevant indicator of neonatal nutritional status [11][15]. Understanding the relationship between birth weight and a wider range of neonatal anthropometric characteristics, including limb and trunk lengths, skinfolds, body breadths and circumferences, may offer novel insight into variation in the proportionality of prenatal growth across the birth weight spectrum and into prenatal growth trade-offs in the context of environmental adaptation or accommodation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the 10th percentile has been more frequently used as a cut-off point for identification of SGA newborns [6][7][8][9] . Similarly, newborns with a birth weight equal to or greater than the 90th percentile are considered large for gestational age (LGA) [6] or well above 2 standard deviations of the reference population. Being heavy for gestational age is related to a greater risk for type I diabetes [10] and possibly also obesity [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated BC of women whose newborns are SGA. Muthayya et al [6] determined that maternal fat-free mass is closely related to BC of the newborn. However, they did not explain how the compartment of fat-free mass was altered in these women.…”
Section: Introductionmentioning
confidence: 99%